THE ROLE OF THE WORLD FOOD PROGRAMME (WFP) IN THE FOOD CRISIS IN CHAD FOR THE PERIOD 2021 - 2023 - IMANUELA JUVENTIA MONTOLALU; THEOPHILOS FREEFA BANOKLEX MARIO IMBIRI; TRESIA PERONIKA; YESSY PUTRI NATASYA (CV KULTURA DIGITAL MEDIA, 2024)
This research explores the impact of the World Food Programme (WFP) in addressing the food crisis in Chad from 2021 to 2023. The WFP, as the world's largest humanitarian organization focused on hunger and food security, plays a crucial role in providing food assistance and nutrition programs to millions of vulnerable people in Chad. Despite challenges such as lack of funding and access to conflict-affected areas, WFP's interventions have helped reduce levels of food insecurity. However, to ensure long-term success in creating food security and improving well-being, closer collaboration between government, international organizations, and local communities is essential. A more comprehensive and collaborative approach is needed to address the complex food crisis in Chad effectively.